2015
DOI: 10.1371/journal.pone.0137975
|View full text |Cite|
|
Sign up to set email alerts
|

Autosomal and mtDNA Markers Affirm the Distinctiveness of Lions in West and Central Africa

Abstract: The evolutionary history of a species is key for understanding the taxonomy and for the design of effective management strategies for species conservation. The knowledge about the phylogenetic position of the lion (Panthera leo) in West/Central Africa is largely based on mitochondrial markers. Previous studies using mtDNA only have shown this region to hold a distinct evolutionary lineage. In addition, anthropogenic factors have led to a strong decline in West/Central African lion numbers, thus, the conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 51 publications
13
62
0
Order By: Relevance
“…Maternal lineage of Gir lions was found to be nested within the clade formed by Northern, Western, and Central African lions (Barnett et al, 2014). Bertola et al (2015) included nuclear markers along with mt-DNA and found lions from India to form a distinct cluster with little/no admixture with African lions. The IUCN Cat Specialist Group now recognizes two subspecies P. leo leo consisting of lions from India, Central and West Africa and P. leo melanochaita comprised of lions from Eastern and Southern Africa (Kitchener et al, 2017).…”
Section: Origin History and Culturementioning
confidence: 98%
“…Maternal lineage of Gir lions was found to be nested within the clade formed by Northern, Western, and Central African lions (Barnett et al, 2014). Bertola et al (2015) included nuclear markers along with mt-DNA and found lions from India to form a distinct cluster with little/no admixture with African lions. The IUCN Cat Specialist Group now recognizes two subspecies P. leo leo consisting of lions from India, Central and West Africa and P. leo melanochaita comprised of lions from Eastern and Southern Africa (Kitchener et al, 2017).…”
Section: Origin History and Culturementioning
confidence: 98%
“…WAP harbors an estimated 350 individuals, or 90% of West Africa's lions (Henschel et al, 2014). Besides lion, WAP harbors an important population of the Critically Endangered Northwest African cheetah Acinonyx jubatus hecki (Belbachir, 2008) and the largest remaining elephant Loxodonta africana population in West Africa (Bouché et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This process was even reflected in the working subspecies definition provided by Kitchener et al (2017), which stated "gene flow is expected between subspecies". For example, extensive nuclear and mtDNA admixture was observed between the African lion subspecies P. l. leo and P. l. melanochaita recognized by Kitchener et al (2017) (Bertola et al 2015(Bertola et al ,2016. In our Bayesian structure analysis that modeled genetic clusters corresponding to the number of subspecies (K = 3) only 5 out of the 70 individuals had mixed ancestry (Q ≤ 0.80).…”
mentioning
confidence: 74%
“…All of these were from Kyrgyzstan and still had most of their ancestry (69-75%) attributed to the appropriate P. u. uncia subspecies (see Figure 2 in Janecka et al 2017). In contrast, a study of lions by Bertola et al (2015) performed similar Bayesian modeling of genetic clusters including runs with the same number (K = 2) as the subspecies defined by Kitchener et al (2017). All of the lions from eastern and southern Africa that Kitchener et al delineated as P. l. melanochaita were assigned to the same genetic cluster as the western P. l. leo (see Figure 2 in Bertola et al 2015).…”
mentioning
confidence: 97%
See 1 more Smart Citation